Multifunctional Materials for Cancer Therapy: From Antitumoral Agents to Innovative Administration - Yipel, Mustafa; V. Ghica, Mihaela; G. Albu Kaya, Madalina; Spoiala, Angela; Radulescu, Marius; Ficai, Denisa; Ficai, Anton; Bleotu, Coralia; Cornelia, Nitipir (Current Organic Chemistry, 2016)
By the developmentof new antineoplastic drugs addressed tospecific sites (key to tumor growth), targeted agents, which do not interfere with most normal cells have many advantages like fewer side effects (as personalized treatment), and prolonged survival time of cancer patients compared to conventional therapy. As current approaches in cancer therapy, drug delivery systems based on polymers (synthetic, natural or combinations like micelles, nanospheres, nanocapsules, nanogels, polymer-drug conjugates, polymer-drug polyplex, polymersomes) are more benefic compared to parent free drug, because of targeted effect of delivery, low toxicity, solubility in biological fluids and immunostimulatory effects. Synthetic polymers (polyesters, polyamides and polyethers) are the most used core materials for drug delivery systems, many of them being officially certified. On the other hand due to their better biocompatibility and biodegradability, the natural ones (polysaccharides and proteins) are still a hot topic on cancer therapy as drug delivery and targeting materials. This article reviews the multifunctional materials used in targeting of drugs with polymer based delivery systems as current-day data and key of future applications on cancer therapy. An increasing interest in the last decades returns to the new, engineered inorganic materials as well as to the newly optimized composites and nanocomposites.
Keywords: polymers